Analisis Penerapan Standar Operasional Prosedur (SOP) Kerja pada PT XLSmart - Atika Putri Rahmawati; Christian Wiradendi Wolor; Eka Dewi Utari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation of Standard Operating Procedures (SOP) at PT XLSmart, focusing on employee understanding, compliance, challenges, and the impact on efficiency and productivity. Using a qualitative case study approach through observation, interviews, and documentation, the findings reveal that most employees understand and follow the SOPs. However, challenges remain, such as discrepancies between written procedures and field conditions, as well as communication gaps between teams that lead to misunderstandings. Despite these issues, SOP implementation has generally contributed positively to work efficiency, organizational clarity, and reduced error rates in daily operations. The study recommends that PT XLSmart regularly review and adjust SOP content to align with real conditions, involve employees in updates, and integrate SOPs into training programs, making them a tool for performance evaluation and professionalism.